ANALISIS MARKETING MIX TERHADAP KEPUTUSAN MENGINAP DI HOTEL GRAND INNA DAIRA PALEMBANG - Krisna Taufik Akbar (2021)
This study aims to analyze and determine the effect of the marketing mix on the decision to stay at the Grand Inna Daira Palembang hotel. Quantitative research methods with a sample of 100 respondents who are guests who stay at the Grand Inna Daira Palembang hotel. The data collection technique was taken through a questionnaire and analyzed using the Statistical Package for the Social Sciences (SPSS) application version 25. Data analysis techniques were through validity tests, reliability tests, classical assumptions, and multiple linear regression tests. Hypothesis testing using the F test, T test and determinant coefficient. The results showed that the variable price, place, product, people, facilities, and process simultaneously had a positive and significant influence on the decision to stay overnight. Partially the variables of price, place, product, and people have a positive and significant impact, while the facilities variable shows a positive but insignificant impact. The process variable partially has no effect on the decision to stay overnight.